Digital Innovation for Seafood Market Expansion: Economic Analysis of Value-Added Products in Pulau Ketam - Dian Septiana Sari; Annisa Ilmi Faried; Tuan Zamilah Binti Tuan Husain; Widia Br, Ginting (Yayasan Multidimensi Kreatif, 2025)
This research investigates the economic potential of market expansion through digital innovation for value-added seafood and herbal products from Pulau Ketam. The study employs a mixed-method approach combining quantitative market analysis and qualitative stakeholder interviews to assess the viability of digital transformation strategies. The research examines current market conditions, digital adoption barriers, and potential economic benefits of implementing innovative technologies in seafood processing and marketing. Results indicate significant opportunities for revenue growth through e-commerce platforms, digital marketing, and value-added product development. The findings reveal that strategic digital innovation can increase market reach by 40-60% and enhance product value by 25-35%. The study concludes that systematic digital transformation, supported by appropriate infrastructure and training programs, can substantially improve the economic sustainability of Pulau Ketam's seafood industry. These findings have important implications for policy makers and industry stakeholders in developing coastal economies through technology-driven market expansion strategies.